2021
DOI: 10.3390/app11146646
|View full text |Cite
|
Sign up to set email alerts
|

Head-Related Transfer Functions for Dynamic Listeners in Virtual Reality

Abstract: In dynamic virtual reality, visual cues and motor actions aid auditory perception. With multimodal integration and auditory adaptation effects, generic head-related transfer functions (HRTFs) may yield no significant disadvantage to individual HRTFs regarding accurate auditory perception. This study compares two individual HRTF sets against a generic HRTF set by way of objective analysis and two subjective experiments. First, auditory-model-based predictions examine the objective deviations in localization cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Many datasets of HRTFs are already available, and several methods have been developed for measuring personal HRTFs in an easy way [ 5 , 6 ]. Various studies show the advantage of using one’s own measured HRTFs in binaural systems [ 7 , 8 ], rather than relying on generic ones.…”
Section: Introductionmentioning
confidence: 99%
“…Many datasets of HRTFs are already available, and several methods have been developed for measuring personal HRTFs in an easy way [ 5 , 6 ]. Various studies show the advantage of using one’s own measured HRTFs in binaural systems [ 7 , 8 ], rather than relying on generic ones.…”
Section: Introductionmentioning
confidence: 99%
“…One study, in particular, confirms improvements in sound source localization by using individual HRTF over generic, but the emphasis is put on the compelling performance of a generic HRTF set [38]. On the other hand, one study found no difference between using individual HRTF and generic HRTF in dynamic virtual environments [39], although their methodology and experimental design are considerably different from the ones presented in this research. The implications of these contradictory findings suggest that additional investigation might help to identify the most informative dynamic cues in order to enhance our comprehension of the variations between the experimental conditions, which may clarify the underlying factors contributing to the observed discrepancies.…”
Section: Discussionmentioning
confidence: 48%
“…In a study involving users of VR technology, researchers compared personalized HRTFs to generic ones [ 8 ]. The study found that, during a static localization test, there was no statistically significant difference in accuracy between personalized and generic HRTFs.…”
Section: Introductionmentioning
confidence: 99%